The Impact of Technology on Education: Transforming Learning in the Digital Age - Jaali, La; Dwiyanto, Dwiyanto; Subaeki, Beki (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze the influence of technology on education and the transformation of learning in the digital era. Rapid technological developments have brought significant changes to learning methods and approaches, enabling the creation of more interactive, flexible, and effective learning experiences. The research method used is the Systematic Literature Review (SLR), which was chosen because it is able to present a comprehensive and structured picture of the results of previous studies. The initial stage of the SLR method is to formulate specific research questions, such as how technology influences learning methods in the digital era, the challenges of implementing technology in education, and strategies for optimizing technology in learning. Furthermore, a literature search was conducted on leading academic databases, such as Google Scholar, Scopus, Web of Science, IEEE Xplore, and ScienceDirect, using keywords such as